Perilaku Keselamatan Dan Kesehatan Kerja Mahasiswa S1 Keperawatan Stikes Borneo Cendekia Medika - Supriyatna, Yayat; Sucipto, Ade (Jurnal Borneo Cendekia, 2024)
Occupational Health and Safety (OHS) is a crucial aspect of the nursing profession, given the high occupational risks involved. Nursing students, as future healthcare professionals, need to develop a strong understanding and adherence to OHS principles early on to protect themselves from workplace accidents and establish professionalism in nursing practice. This study aims to analyze the occupational health and safety behaviors of undergraduate nursing students at STIKES Borneo Cendekia Medika and identify the factors influencing their compliance with OHS standards.This study employs a quantitative approach using survey techniques involving nursing students engaged in laboratory and clinical practice activities. The findings indicate a positive correlation between students’ knowledge levels and their compliance with OHS practices, aligning with the Theory of Planned Behavior (TPB), which states that individual behavior is influenced by attitudes, subjective norms, and perceived behavioral control. Students with a higher understanding of OHS tend to be more disciplined in implementing workplace safety standards.The study results show that 70% of students fall into the "good" category of OHS knowledge, 24% have a moderate level of knowledge, and 6% demonstrate a low level of understanding. These findings indicate that while most students possess a solid knowledge base, a portion still lacks sufficient comprehension. Factors contributing to this include a lack of continuous education and training on OHS regulations, limited access to safety facilities, insufficient hands-on practice, and a weak safety culture in academic and clinical environments.These findings highlight the need for strengthening OHS education, simulation-based training, improved safety infrastructure, and the development of a strong safety culture in both academic and clinical settings to enhance students’ compliance with OHS standards.